PENERAPAN MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI TEKS PROSEDUR PADA PESERTA DIDIK KELAS IV SD NEGERI 2 ABEPURA - Tangguling, Riska; Dian Septikasari; Warikar, Amelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on improving students’ learning outcomes Indonesian language, particularly in procedure text, through the use of Wordwall media. The study employed a Classroom Action Research (CAR) design based on the spiral model by Kemmis & McTaggart (Kemmis et al., 2014) and was conducted in two cycles involving 27 fourth-grade students at SD Negeri 2 Abepura. The instruments used consisted of learning outcome tests and observation sheets used to monitor students’ activities during the learning process. The results of the study showed an improvement in students’ learning outcomes in each cycle. at the pre-action stage, only 8 students (29,63%) met the Learning Objective Achievement Criteria (LOAC) with an average score of 58,41. After the implementation of cycle I, the number of students who met the criteria increased to 20 students (74,07%) with a class average score of 80,3. In cycle II, all students achieved completeness (100%) with an average score of 83,56. Thus, it can be concluded that the use of Wordwall media is effective in enhancing students’ Indonesian language learning outcomes, particularly in procedure text, among fourth-grade students at SD Negeri 2 Abepura.